Urinary sulphatoxymelatonin as a biomarker of serotonin status in biogenic amine-deficient patients - Batllori, Marta; Opladen, Thomas (Scientific reports, 2017)
Melatonin is synthesized from serotonin and it is excreted as sulphatoxymelatonin in urine. We aim to evaluate urinary sulphatoxymelatonin as a biomarker of brain serotonin status in a cohort of patients with mutations in genes related to serotonin biosynthesis. We analized urinary sulphatoxymelatonin from 65 healthy subjects and from 28 patients with genetic defects. A total of 18 patients were studied: 14 with autosomal dominant and recessive guanosine triphosphate cyclohydrolase-I deficiency; 3 with sepiapterin reductase deficiency; and 1 with aromatic L-amino acid decarboxylase deficiency. Further 11 patients were studied after receiving serotoninergic treatment (serotonin precursors, monoamine oxidase inhibitors, selective serotonin re-uptake inhibitors): 5 with aromatic L-amino acid decarboxylase deficiency; 1 with sepiapterin reductase deficiency; 3 with dihydropteridine reductase deficiency; and 2 with 6-pyruvoyltetrahydropterin synthase deficiency. Among the patients without therapy, 6 presented low urinary sulphatoxymelatonin values, while most of the patients with guanosine triphosphate cyclohydrolase-I deficiency showed normal values. 5 of 11 patients under treatment presented low urine sulphatoxymelatonin values. Thus, decreased excretion of sulphatoxymelatonin is frequently observed in cases with severe genetic disorders affecting serotonin biosynthesis. In conclusion, sulphatoxymelatonin can be a good biomarker to estimate serotonin status in the brain, especially for treatment monitoring purposes.
Gesehen am 10.09.2018